2019
DOI: 10.1104/pp.19.00618
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Tocopherol Biosynthesis in Arabidopsis Basal Immunity to Bacterial Infection

Abstract: ORCID IDs: 0000-0003-4828-958X (M.H.); 0000-0002-9532-8687 (N.S.); 0000-0002-8703-5403 (J.Z.).Tocopherols are lipid-soluble antioxidants synthesized in plastids of plants and other photosynthetic organisms. The four known tocopherols, a-, b-, g-, and d-tocopherol, differ in number and position of methyl groups on their chromanol head group. In unstressed Arabidopsis (Arabidopsis thaliana) leaves, a-tocopherol constitutes the main tocopherol form, whereas seeds predominantly contain g-tocopherol. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 123 publications
1
26
0
6
Order By: Relevance
“…To determine the levels of Pip, NHP, SA, SAG, NHP-hexose, and lysine in the leaves of the different species, the gas chromatography-mass spectrometry-based analytical procedure previously established for Arabidopsis was used (detailed in Hartmann et al , 2018 ; Stahl et al , 2019 ). For metabolic analyses of cucumber phloem sap, the above-described filter paper extracts were supplemented with 900 µl of MeOH/H 2 O (80:20, v/v) and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the levels of Pip, NHP, SA, SAG, NHP-hexose, and lysine in the leaves of the different species, the gas chromatography-mass spectrometry-based analytical procedure previously established for Arabidopsis was used (detailed in Hartmann et al , 2018 ; Stahl et al , 2019 ). For metabolic analyses of cucumber phloem sap, the above-described filter paper extracts were supplemented with 900 µl of MeOH/H 2 O (80:20, v/v) and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…If not removed immediately, PL-OOH can undergo fragmentation to form highly toxic lipid radicals and other reactive lipid breakdown products (Schneider et al 2008). Non-enzymatic systems preventing uncontrolled accumulation of PL-OOH include chelators of iron and lipophilic radical-trapping antioxidants, especially ɑ-and ɣ-tocopherol (Kanwischer et al 2005;Stahl et al 2019;. In contrast to the primary function of tocopherols at the plasma membrane in mammalian cells, their protective function in plants, however, is primarily exerted at the chloroplast membrane (Maeda and DellaPenna 2007).…”
Section: Paradigm Shift 4: Thiol Peroxidases Link Ros To Functional Rmentioning
confidence: 99%
“…The production of these molecules is a metabolic innovation allowing plants to live under high-oxygen conditions (Das and Roychoudhury, 2014), as their roles protecting photosystem II against oxygen singlets and limiting lipid peroxidation are well documented (Krieger-Liszkay and Trebst, 2006;Miret and Munné-Bosch, 2015). More recently, it was demonstrated that the tocopherol biosynthetic pathway modulates salicylic acid accumulation, affecting basal resistance against Pseudomonas syringae in Arabidopsis plants (Stahl et al, 2019). Furthermore, tocopherols were found to be required for a retrograde chloroplast-to-nucleus signaling mechanism favoring micro RNA biogenesis under abiotic stress (Fang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%